Pure spinor superstring partition function - Arroyo Montero, E. A [UNESP] (2008)
In this thesis, we have calculated the partition function of pure spinors. The computation is performed by using two different methods, namely ghosts-for-ghosts (up to the twelth mass-level) and fixed point (up to the fifth mass-level) techniques. After adding the contribution from the ('qui POT. m, 'teta POT. alfa', 'rô IND. alfa') matter variables, we reproduce the massive open superstring spectrum. Even though pure spinor variables are bosonic, the pure spinor partition function contains fermionic states which first appear at the second mass-level. These fermionic states come from functions which are not globally defined in pure spinor space, and are related to the b ghost in the pure spinor formalism for the superstring